Developing an In-house Interdisciplinary Three-Dimensional Service: Challenges, Benefits, and Innovative Health Care Solutions. Issue 7 (October 2018) - Hatamleh, Muhanad M.; Ong, Juling; Hatamleh, Zaydoon Mohammad; Watson, Jason; Huppa, Chrisopher
Abstract : Abstract: Three-dimensional printing (3DP) technologies have been employed in regular medical specialties. They span wide scope of uses, from creating 3D medical models to design and manufacture of Patient-specific implants and guidance devices which help to optimize medical treatments, patient education, and medical training. This article aims to provide an in-depth analysis of factors and aspects to consider when planning to setup a 3D service within a hospital serving various medical specialties. It will also describe challenges that might affect 3D service development and sustainability and describe representative cases that highlight some of the innovative approaches that are possible with 3D technology. Several companies can offer such 3DP service. They are often web based, time consuming, and requiring special call conference arrangements. Conversely, the establishment of in-house specialized hospital-based 3D services reduces the risks to personal information, while facilitating the development of local expertise in this technology. The establishment of a 3D facility requires careful consideration of multiple factors to enable the successful integration with existing services. These can be categorized under: planning, developing and sustaining 3D service; 3D service resources and networking workflow; resources and location; and 3D services quality and regulation management.